2020
DOI: 10.1002/cssc.202000407
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Based Bimetallic Nanocrystal Catalysts for the Direct Synthesis of Hydrogen Peroxide

Abstract: The direct synthesis of H2O2 from H2 and O2 is a strongly desired reaction for green processes and a promising alternative to the commercialized anthraquinone process. The design of efficient catalysts with high activity and H2O2 selectivity is highly desirable and yet challenging. Metal dopants enhance the performance of the active phase by increasing reaction rates, stability, and/or selectivity. The identification of efficient dopants relies mostly on catalysts prepared with a random and non‐uniform deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 83 publications
0
43
0
Order By: Relevance
“…Whereas previously catalysts were mostly tested in a narrow window of H 2 : O 2 ratios with excess of O 2 , 1,[10][11][12]14 in this work the H 2 : O 2 ratio was varied from 10 : 1 to 1 : 10 and it was found that trends in activity and stability of the catalysts strongly depend on the H 2 : O 2 ratio (Fig. 2).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Whereas previously catalysts were mostly tested in a narrow window of H 2 : O 2 ratios with excess of O 2 , 1,[10][11][12]14 in this work the H 2 : O 2 ratio was varied from 10 : 1 to 1 : 10 and it was found that trends in activity and stability of the catalysts strongly depend on the H 2 : O 2 ratio (Fig. 2).…”
Section: Discussionmentioning
confidence: 80%
“…† Detailed characterisation (TEM, EDX mapping, XRD, XAS) of the isolated unsupported bimetallic nanoparticles and the supported catalysts is reported in our recent publication. 14 TEM analysis reported in the cited work 14 reveals relatively broad NP size distribution between 2 and 6 nm with maxima at 3-4 nm.…”
Section: Catalyst Synthesismentioning
confidence: 90%
See 2 more Smart Citations
“…The H 2 O 2 concentration was analyzed ex situ by UV-Vis spectroscopy. 16 Accordingly, the as-prepared TiO 2 -Pd HNS exhibit a H 2 O 2 selectivity of 47% with a productivity of 1850 mol kg Pd −1 h −1 (Fig. 5e and f ).…”
Section: Direct Synthesis Of H 2 O 2 and Co Oxidationmentioning
confidence: 89%